The Teacher, The Doctor, and The Judge: Power and Authorities in Pink Floyd’s The Wall - Boza Méndez, David (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2017)
The following investigation focuses on power relations in Pink Floyd’s The Wall. Speci cally, this article centers on the images of authorities on the album: the teacher, the physician, and the judge. The literary analysis of these characters supported by notions developed by theorists on the subject of power leads to signi cant conclusions on the matter. La siguiente investigación tiene por objetivo analizar las relaciones de poder en The Wall de Pink Floyd. El presente artículo se centra en las imágenes de autoridad en el álbum: el profesor, el médico y el juez. El análisis literario de estos personajes con base en preceptos críticos desarrollados por varios especialistas en el campo de la teoría del poder llevará a conclusiones signi cativas.